The tidal volume fix and more… - Simonis, Fabienne D.; Neto, Ary Serpa; Schultz, Marcus J. (Journal of Thoracic Disease, 2019)
In the past 30 years the medical literature has been enriched with numerous publications reporting on randomized clinical trials, meta-analysis and service reviews on invasive ventilation in critically ill patients (Figure 1). For many years the investigations on lung-protective ventilation focused on patients with acute respiratory distress syndrome (ARDS). Interest in the effects of lung-protective ventilation in patients without ARDS is rapidly increasing, however, resulting in a steep rise of the number of publications on lung-protection in patients without ARDS.